2013
DOI: 10.1523/jneurosci.3878-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Orchestrate Divergent Effects on Mood through Adult Neurogenesis

Abstract: Both social defeat stress and environmental enrichment stimulate adrenal glucocorticoid secretion, but they have opposing effects on hippocampal neurogenesis and mood. Hypothalamic-pituitary-adrenal (HPA) axis dysregulation and decreased neurogenesis are consequences of social defeat. These outcomes are correlated with depressive states, but a causal role in the etiology of depression remains elusive. The antidepressant actions of environmental enrichment are neurogenesis-dependent, but the contribution of enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
140
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(149 citation statements)
references
References 75 publications
5
140
1
3
Order By: Relevance
“…A previous study showed that the effects of social defeat stress and environmental enrichment on both neurogenesis and stress-related behavior are dependent on modulation of the HPA axis, as adrenalectomized mice with clamped CORT levels were unaffected by these environmental manipulations (Lehmann et al, 2013). Data presented here further suggests that CORT-mediated changes in neurogenesis are required for behavioral effects, as mice with increased neurogenesis do not display CORT-induced behavioral effects.…”
Section: Discussionsupporting
confidence: 66%
“…A previous study showed that the effects of social defeat stress and environmental enrichment on both neurogenesis and stress-related behavior are dependent on modulation of the HPA axis, as adrenalectomized mice with clamped CORT levels were unaffected by these environmental manipulations (Lehmann et al, 2013). Data presented here further suggests that CORT-mediated changes in neurogenesis are required for behavioral effects, as mice with increased neurogenesis do not display CORT-induced behavioral effects.…”
Section: Discussionsupporting
confidence: 66%
“…In the current study, the number of newly formed astrocytes, as marked by GFAP/BrdU double-labeling, in the dentate gyrus did not vary with RSD when examined at The attenuation in the number of neurons was evident in the caudal hippocampus of RSD-exposed mice compared to the controls. This region-specific differential effect of social defeat stress on neurogenesis has also been demonstrated in previous studies [38]. Moreover, existing literature exploring the functional dichotomy of the hippocampus implicates the rostral and the caudal hippocampus in cognitive and affective processing respectively [39].…”
Section: Discussionsupporting
confidence: 74%
“…Although depression was traditionally considered to have a neurochemical basis, structural connectivity and plasticity changes, including neurogenesis, may contribute to its etiology as well. Later studies have suggested that neurogenesis is implicated in antidepressant drug action (Perera et al 2011;Surget et al 2011), but it remains elusive how exactly newborn neurons contribute to mood and depression, besides their cognitive deficits, which are related, but not specific to mood disorders (Revest et al 2009;Snyder et al 2011;Anacker and Pariante 2012;Lehmann et al 2013;Lucassen et al 2013a,b).…”
Section: Neurogenesis and Depressionmentioning
confidence: 99%